2010
DOI: 10.1088/0953-4075/43/4/045502
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of multipartite entanglement in the non-Markovian environments

Abstract: We consider the entanglement dynamics of N qubits interacting with independent structured reservoirs. The system is initially prepared in the multipartite Greenberger–Horne–Zeilinger (GHZ)-type state. We study the dependence of the entanglement dynamics on both the qubit number N and the purity of initial state, and show that the qubit number N and the purity can control the time of appearance of the N-qubit entanglement sudden death and the entanglement sudden birth of the reservoirs. Also based on the purity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…Finally, the PL n is found to be the most harmful to the dynamics of the purity, coherence and information, with saturation levels reaching earlier, especially for large g values. The single qutrit system's quantitative degradation is partial, which contradicts most of the earlier results, for example, those given in [19,26,33,34,43]. Most significantly, we found the decay rate to be greatly regulated by altering the values of g, which directly increases as this parameter is increased.…”
Section: Classical Field With Pl Ncontrasting
confidence: 99%
See 2 more Smart Citations
“…Finally, the PL n is found to be the most harmful to the dynamics of the purity, coherence and information, with saturation levels reaching earlier, especially for large g values. The single qutrit system's quantitative degradation is partial, which contradicts most of the earlier results, for example, those given in [19,26,33,34,43]. Most significantly, we found the decay rate to be greatly regulated by altering the values of g, which directly increases as this parameter is increased.…”
Section: Classical Field With Pl Ncontrasting
confidence: 99%
“…There was no evidence of ESD or ESB, and both noisy parameters showed a monotonic reduction. As a result, there is no way for information from the environment to flow back into the system, contradicting the findings of [19,24,28,42,43]. Because of this noise, purity, coherence and information are permanently lost rather than experiencing periodic transitory deterioration.…”
Section: Classical Field With Pl Nmentioning
confidence: 94%
See 1 more Smart Citation
“…Applying control techniques allows systems to suppress decoherence [25,26]. On the other hand, there are some situations in which the interactions between the quantum system and environment can produce quantum correlations such as entanglement revival [27,28]. In other words, environments may operate as control elements for these cases [29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the study of the essential features of entanglement and its dynamical behavior under the decoherence of relevant quantum system have attracted much attention in recent years [2][3][4][5][6][7][8][9][10][11]. Yu and Eberly in [2] found that the entanglement of qubits under the Markovian decoherence can be terminated in a finite time despite the coherence of single qubit losing in an asymptotical manner [2].…”
Section: Introductionmentioning
confidence: 99%